Implementation of Librarian Functional Position Career Development Policy (Study at Malang State University) - Achmad Qorni Novianto; Andy Fefta Wijaya; Lely Indah Mindarti (Wacana Journal of Social and Humanity Studies, 2019)
The government has issued career development policies since 1988, until the issuance of Permenpan-RB Number 9 of 2014, but implementation of Permenpan-RB Number 9 of 2014 still leaves some challenges. The objectives of this study are:  (1) to explain the implementation of Permenpan-RB Number  9  of  2014  at  Malang  State  University  (UM);  and  (2)  knowing the supporting and inhibiting factors. This study uses descriptive qualitative methods. Data collection techniques used in this study were interviews, observation, and documentation. The data analysis used in this study is the  Miles, Huberman and Saldana  analysis models. Research findings:  (1)  the  reluctance  of  a  small  number  of  librarians  to  take  part  in  the  librarianship competency test and carry out professional development activities, (2) the placement of general functional personnel who do not have competence in the library sector to carry out librarians activities due to the lack of librarians and (3) submission cancellations promotion of UM librarians to Main Librarian Position due to limitation of librarianship career paths to positions of middle librarians at Kemenristekdikti. The inhibiting factors for the implementation of Permenpan-RB Number 9 of 2014 in UM are (1) the lack of responsiveness of the Kemenristekdikti in processing proposals for promotion/rank of librarians, and (2) the limited number of competent civil servants to follow in passing the position of librarians. The implementation of Permenpan-RB Number 9 of 2014 in MUs has not been going well, therefore, a fast response from both librarians and UM leaders is needed to minimize the gap.